2011
DOI: 10.1167/11.11.157
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious pop-out: Attentional capture by unseen feature singletons only when top-down attention is available

Abstract: Visual "pop-out" occurs when a unique visual target (e.g. a feature singleton) is present among a set of homogeneous distractors. However, the role of visual awareness in this process remains unclear. Here we show that, even though subjects were not aware of a suppressed pop-out display, their subsequent performance on an orientation discrimination task was significantly better at the pop-out location than at a control location. These results indicate that visual awareness of a feature singleton is not necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
46
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 31 publications
13
46
1
1
Order By: Relevance
“…In line with this possibility, recent studies have shown that exogenous attention can be summoned by monocular supraliminal onsets in a spatialcueing paradigm (Self & Roelfsema, 2010). In addition, and even more relevant to the present hypothesis, it has been found that attention (and eye movements) can also be unconsciously shifted toward a suppressed target singleton during CFS (Hsieh, Colas, & Kanwisher, 2011;Rothkirch, Stein, Sekutowicz, & Sterzer, 2012;Zhaoping, 2008).…”
Section: Discussionsupporting
confidence: 77%
“…In line with this possibility, recent studies have shown that exogenous attention can be summoned by monocular supraliminal onsets in a spatialcueing paradigm (Self & Roelfsema, 2010). In addition, and even more relevant to the present hypothesis, it has been found that attention (and eye movements) can also be unconsciously shifted toward a suppressed target singleton during CFS (Hsieh, Colas, & Kanwisher, 2011;Rothkirch, Stein, Sekutowicz, & Sterzer, 2012;Zhaoping, 2008).…”
Section: Discussionsupporting
confidence: 77%
“…Although several findings indicate that certain visual properties of stimuli suppressed from awareness can nevertheless guide spatial attention (58,59), there is no clear evidence that stimuli suppressed through CFS are processed semantically. We discuss some caveats to this conclusion in the SI Results and Discussion, Semantic Processing of Images Made Invisible by Continuous Flash Suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Visual attention based algorithm reveals the mechanisms of biological visual intelligence [15][16][17][18][19]. It has wide applications in various locations as reported by some computer vision researchers [20][21][22][23][24][25][26].…”
Section: An Improved Visual Attention Based Algorithmmentioning
confidence: 99%